The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.2298/avb0506483p
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium supplementation of pigs and broilers as a way of producing selenium enriched meat

Abstract: Serbia is a selenium (Se) deficient area. In the food chain animals accumulate Se in tissues, thus meat is a good source of this microelement. The aim of the research is to study the effects of different forms and doses of dietary Se in pigs and broilers on muscle and liver tissue Se concentrations, as well as to assess the possibility of using selenized meat as a Se source in the Belgrade area. Pigs (24) were randomly assigned in 4 groups: control and groups supplemented with Na-selenite: 0.10, 0.30 mgSe/kg f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…These outcomes consistently confirmed that the efficacy of Se from Seenriched yeast and HPSeKS was comparable, but higher than that of Se from sodium selenite when used tissue Se concentration as an indicator [19]. Numerous reports similarly observed broilers received Se from Se-enriched yeast or Seenriched alga had higher (p<0.05) tissue Se content than those received Se from sodium selenite [4,5,7,8,38,39]. On the other hand, Se from Se-enriched garlic, cabbage [10], and malt [40] did not improve Se concentrations in chick tissues, reflecting that selenomethionine is not the major Se species in these plants.…”
Section: Discussionsupporting
confidence: 63%
“…These outcomes consistently confirmed that the efficacy of Se from Seenriched yeast and HPSeKS was comparable, but higher than that of Se from sodium selenite when used tissue Se concentration as an indicator [19]. Numerous reports similarly observed broilers received Se from Se-enriched yeast or Seenriched alga had higher (p<0.05) tissue Se content than those received Se from sodium selenite [4,5,7,8,38,39]. On the other hand, Se from Se-enriched garlic, cabbage [10], and malt [40] did not improve Se concentrations in chick tissues, reflecting that selenomethionine is not the major Se species in these plants.…”
Section: Discussionsupporting
confidence: 63%
“…In recent years, considerable attention has been paid to supplementing animal feed with organically bound selenium in Se-enriched yeast as an alternative to inorganic Se supplementation. The use of organic Se sources generally results in better absorption, more effective utilization and formation of larger body deposits of this microelement [12][13][14][15][16]. Se-enriched yeast obtained by Saccharomyces cerevisiae cultivation with inorganic Se source may contain >90% of its Se in the form of selenomethionine (SeMet) [17].…”
Section: Introductionmentioning
confidence: 99%
“…A prevention of Se deficiency can be performed by dietary supplementation. The supply of Se in the diet depends on the country, the region, its concentration in the environment and the type of food intake (Olivera et al, 2005;Pilarczyk et al, 2010;Fairweather-Tait et al, 2011). Much of Europe, including some Polish regions, are considered areas poor in Se (Pilarczyk et al, 2008(Pilarczyk et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%